Analisis validitas dan praktikalitas lembar kerja siswa berbasis konflik kognitif pada materi gerak lurus dan gerak parabola - Annisa Fadhilah; Fatni Mufit; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2020)
The era of the industrial revolution 4.0 which is very influential in human life today, especially in the field of education to create better generations for the nation. Education is demanded to be able to improve qualified human resources. The 2013 revised 2017 curriculum was an attempt by the government to answer the demands of the industrial revolution 4.0 era which aims to shape the character and competence and literacy of students. However, the reality on the ground showed that student literacy has not been implemented well. One solution to overcome these problems is to develop a cognitive conflict based Physics Worksheet. The purpose of this research was to determine the validity, practicality and effectiveness of the student worksheet Physics based on cognitive conflict. This type of research is Development Research using the Plomp model. The object of the research was cognitive conflict based student worksheet. Data source validation results from experts by the Physics lecturer at the Faculty of Mathematics and Natural Sciences UNP, the results of practicality by Physics teachers, as well as the results of the practicality of one to one and small groups and effectiveness by students of class X SMAN 7 Padang. The data analysis technique used were descriptive statistical analysis for product validation and practicality and for the effectiveness of using the percentage technique seen from differences in pretest and posttest. The results of data analysis from the research that has been done as following. First, the cognitive conflict based worksheet has a very strong validity with an average value of 86.35. Second, the use of cognitive conflict-based worksheets has a very strong practicality with an average grade of one to one and small group students respectively at 87.32 and 90.90. Third, the use of cognitive conflict based LKS on straight motion and parabolic motion material is effectively used in the learning process to improve students' new literacy. So, it can be concluded that the worksheet based on cognitive conflict in the material of straight motion and parabolic motion is valid, practical, and effective in increasing the new literacy of class X high school students.